EFFORTS TO INCREASE STUDENT LEARNING MOTIVATION THROUGH THE APPLICATION OF THE TEAM GAMES TOURNAMENT (TGT) MODEL IN LEARNING MATHEMATICS CLASS V SDN CIJANTUNG 05 MORNING - Dwi Aprilia, Devita (Prima: Jurnal Pendidikan Matematika, 2024)
This study was conducted with the aim of being able to increase student learning motivation through the application of the Team Games Tournament (TGT) model in mathematics learning, the research subjects used were grade V students of SDN Cijantung 05 Pagi totaling 26 students with the method of Classroom Action Research (PTK) with a collaborative system, this research was conducted 2 cycles The data obtained in this study from the results of questionnaire sheets and observation sheets. The results obtained from this study are an increase in motivation to learn mathematics, in cycle 1 student learning motivation increased with a percentage of 73.3% that previously in pre-cycle research student learning motivation was very low at 43.11% so that it fell into the category of very lacking and incomplete. Whereas in cycle 2 student learning motivation increased again with a percentage of 86.23%. So that this research was declared successful because it reached the good category (complete) by reaching the ideal value of 75. In addition, the increase in student learning motivation in the application of the Team Games Tournamnet (TGT) model can be evidenced from the results of student activity actions during 2 meetings in cycle 1 and cycle 2, the results of student activity actions shown in cycle 1 were 68% and 72% while in cycle 2 they were 77.3% and 85.3% of these results it can be said that the application of the Team Games Tournament (TGT) model can increase student motivation in learning mathematics, because the application of the model can help teachers in creating an interesting, fun learning model, and can develop motivation and self-confidence in their varied abilities.